2005
DOI: 10.1093/chemse/bji061
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Aroma on Work Efficiency: Lavender Aroma during Recesses Prevents Deterioration of Work Performance

Abstract: The present study investigated whether exposure to aromas during recess periods affects work performance. Subjects comprised 36 healthy male students (mean age, 24.2 +/- 2.2 years) who were randomly divided into three groups: (1) control group, not exposed to aroma during recesses; (2) jasmine group, exposed to jasmine aroma during recesses; and (3) lavender group, exposed to lavender aroma during recesses. All participants completed five work sessions performing a task requiring concentration on a computer mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 19 publications
2
46
0
1
Order By: Relevance
“…In vitro tests have demonstrated that lavender oil has analgesic (Silva et al 2015) and anaesthetic effects (Ghelardini et al 1999). Lavender scent in the room prevents deterioration in work performance (Sakamoto et al 2005), may improve memory and the health state of people with Alzheimer's disease (Adsersen et al 2006). Lavender essential oil helps treat diseases of the digestive tract; it exhibits a diastolic effect for the ileum and smooth muscles (Lis-Balchin and Hart 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro tests have demonstrated that lavender oil has analgesic (Silva et al 2015) and anaesthetic effects (Ghelardini et al 1999). Lavender scent in the room prevents deterioration in work performance (Sakamoto et al 2005), may improve memory and the health state of people with Alzheimer's disease (Adsersen et al 2006). Lavender essential oil helps treat diseases of the digestive tract; it exhibits a diastolic effect for the ileum and smooth muscles (Lis-Balchin and Hart 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested (−)-bornyl acetate or pine essential oil including (−)-bornyl acetate had a sedative effect by breathing (1, 11). The olfactory stimulation with sedative-type essential oils or a compound could improve the performance (8,18,21,27). These information together with our results suggested that the dose of volatile compound is important for performance.…”
Section: Resultsmentioning
confidence: 99%
“…8) Conversely, another study found that the administration of an odor stimulus (peppermint) via the nasal cannula did not decrease the latency for the detecting a task at the end of the work, while the periodic delivery of a tactile stimulus did. 9) The conflicting results of these studies are mainly due to the lack of a standardized experimental protocol, different researchers using not only different kinds of odors but various research methods for exposing the subjects to the odors.…”
Section: )mentioning
confidence: 97%